The prevalence and usage of mobile health applications among mental health patients in Saudi Arabia. (March 2018) - Atallah, Nora; Khalifa, Mohamed; El Metwally, Ashraf; Househ, Mowafa
Highlights: Mobile applications have provided researchers from all over the world with the opportunity to discover new methods of enabling and engaging patients. It is important to explore the prevalence of mobile health applications for mental health patients and to measure their interest and willingness to use their smartphones to record and track their own health. Using interactive mobile applications for patients with depression and anxiety may unlock greater benefits to patients and providers. Empowering patients to access, interact, record events, and be part of the care provided is a major benefit to the health care system delivery in general. The development of mental health related mobile application should consider age, language, disease specificity, privacy, security and means of collecting data and analyzing them. Abstract: Background: Mobile health (mHealth) applications provide new methods of engagement with patients and can help patients manage their mental health condition. Objective: The main objective of this study is to explore the prevalence of the use of mobile health applications for mental health patients in Saudi Arabia. Methods: A total of 376 participants with depression and/or anxiety completed an online survey distributed by social networks which asked questions relating to mobile phone ownership, uses of health applications, and utilization patterns to track mental health related issues. Results: Approximately, 46% of the participants reported running one or two healthcare related applications on their mobile phones. In all age groups, 64% of the participants used their mobile phones to access information related to their own health. Also, 64% of the participants expressed interest in using their own mobile phones to track and follow the progression of their depression and/or anxiety. Conclusions: Developing mobile health applications for Saudi mental health patients is needed since it can offer opportunities for patients, researchers, caregivers, and legislators to work together to improve the state of mental health care in Saudi Arabia.